Design and Modeling of Controllers for Aircraft Pitch Contol Movement (International Journal of Engineering and Computer Science, 2018)
In the present paper intelligent controllers design methodology is presented to examine their overall performance primarily based on time response specification for controlling Pitch movement of aircraft. The aircraft pitch control system is designed for Linear and Non-linear models and the effect of various nonlinearities is studied based on the overall performance of various controllers in Flight control system (FCS). The controllers are designed based on linearized model of aircraft so as to simplify the design process, with the idea of dynamic modeling of Servomotor which is used to control the movement of elevators. Elevators are control surfaces which are used to control longitudinal motion of aircraft by deflecting the flow of air and creating differential pressure on the wings. Aircraft pitch control movement is categorized under the longitudinal motion. The movement of these control surfaces is performed through Servomotors, for which mathematical modeling is provided. A baseline reference controller is used for determining the performance of other controllers and making a detail comparison. So while developing the other controllers we took Fuzzy Logic Controller as reference as carry forwarded the original cased study. A new hybrid combination of Fuzzy-PID with fuzzy compensation and ANN-PID Controller has been developed for controlling the pitch movement of aircraft for this particular model. A quantitative analysis of these controllers has been carried out in MATLAB Simulink© environment. It is concluded that combination of ANN-PID controller provides best results for Linear as well as Non-linear aircraft pitch control models.